THE RELEVANCE OF NUTRITIONAL STATUS AND HISTOPATHOLOGICAL FINDINGS ON THE INFECTIOUS PROCESS OF BALB/C MICE INOCULATED WITH Lacazia loboi - BARBOSA, Adriana Sierra Assencio Almeida; DIÓRIO, Suzana Madeira; PEDRINI, Silvia Cristina Barboza; NUNES, Adauto José Ferreira; BELONE, Andréa de Faria Fernandes; SILVA, Sônia Maria Uso Ruiz; SARTORI, Beatriz Gomes Carreira; CALVI, Sueli Aparecida; VILANI-MORENO, Fátima Regina; PEREIRA, Paulo Câmara Marques (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
The aim of this study was to evaluate the effects of the protein-calorie malnutrition in BALB/c isogenic mice infected with Lacazia loboi, employing nutritional and histopathological parameters. Four groups were composed: G1: inoculated with restricted diet, G2: not inoculated with restricted diet, G3: inoculated with regular diet, G4: not inoculated with regular diet. Once malnutrition had been imposed, the animals were inoculated intradermally in the footpad and after four months, were sacrificed for the excision of the footpad, liver and spleen. The infection did not exert great influence on the body weight of the mice. The weight of the liver and spleen showed reduction in the undernourished groups when compared to the nourished groups. The macroscopic lesions, viability index and total number of fungi found in the footpads of the infected mice were increased in G3 when compared to G1. Regarding the histopathological analysis of the footpad, a global cellularity increase in the composition of the granuloma was observed in G3 when compared to G1, with large numbers of macrophages and multinucleated giant cells, discrete numbers of lymphocytes were present in G3 and an increase was observed in G1. The results suggest that there is considerable interaction between Jorge Lobo's disease and nutrition.